Structural Numerical Modelling Applied to the Capillary Barrier Effect Overburden of Acidic Tailings Ponds - Du, Jianghong; Xiong, QiuLing; Xun, Ailing; Zhang, Lu (Journal of Research in Science and Engineering, 2025)
The issue of treating Acid Mine Drainage (AMD) has become a significant environmental concern for the global mining industry in recent years. AMD is generated by the leaching of sulfur-containing minerals (mainly pyrite, FeS2) in mine tailings, which react with atmospheric oxygen to form highly acidic solutions. These solutions contain heavy metal ions and pose significant risks to water bodies, soil, and human health. Moreover, the presence of AMD has been demonstrated to contribute to severe ecological damage, including the impairment of aquatic life through the induction of hypoxia in fish and other organisms. In light of the considerable impact of AMD, the treatment of this phenomenon has become an indispensable component of mining operations. The present study concentrates on the numerical simulation of the Capillary Barrier Effect Cover(CCBE)system applied to acid mine tailings. The CCBE consists of three layers: a coarse-grained soil layer at the base, a fine-grained soil layer in the middle, and a topsoil layer to prevent evaporation. The present study aims to analyse the influence of different structural conFigure urations and material properties on the oxygen barrier performance of the CCBE, with particular focus on the effect of layer thickness on the system's efficiency in maintaining high saturation levels and preventing oxygen ingress into the tailings.